Synthesis, Characterization and Complexation of Sc(III) Ion Using Chloroquine Diphosphate Drug - Otuokere, I. E.; Okpara, L. O.; Ikpo, N.; Okafor, G. U.; Nwadire, F. C.; Olisa, C. O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Chloroquine possess lone pairs of electrons that can be donated to central metal ion. Scandium (III) complex of chloroquine was synthesized by reaction of chloroquine diphosphate with scandium (III) oxide. The metal complex was characterized based on melting point, UV, IR, and 1H NMR Spectroscopy. 1H NMR Spectra of the complex further showed the involvement of the amine group in coordination to the metal complex. The IR spectra of the complex showed the involvement of amine and imine group in coordination to the metal. The electronic spectrum of the complex suggested intraligand charge transfer (ILCT), ligand to metal charge transfer (LMCT), and d-d transition. The melting point of the complex was higher than the free ligand. Spectroscopic studies showed that chloroquine acted as a bidentate ligand. These results showed that chloroquine has the ability to sequestrate Sc (III) ion from solution. We recommend the use of chloroquine in scandium extraction and chelation therapy.